Ботаніко-екологічна характеристика деревно-чагарникових насаджень Довгинцівського дендропарку (м. Кривий Ріг) - Savos'ko, V.M.; Kopych, O.U. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
Trees and shrub planting at Dovhyntsivo Park (Kryvyi Rih, Dnepropetrovs’k reg.) presented 74 species belonging to 57 genera and 27 families. Most of the rocks park characterized medium-high level of vitality, middle and high level of decoration. The living condition leading stands (oak, pine and birch) is assessed as weak and very weak. Estimation characteristics of stands of Betula pendula Roth and Pinus sylvestris L. forest hung in a park above the data table growth forest species, while stands of Quercus robur L. – match these values.